Influence of rheological and fresh-state properties on formwork pressure of self-compacting concrete - Mouhcine Benaicha; Olivier Jalbaud; Xavier Roguiez; Adil Hafidi ALaoui; Yves Burtschell (Results in Engineering, 2025)
Abstarct: This study details an experimental analysis of the effect of rheological parameters and fresh-state properties of self-compacting concrete (SCC) on the formwork pressure exerted by it. Twenty-one different SCC mixtures were manufactured with increasing concentrations of air entraining agent (AEA), thereby resulting in systematic changes to yield stress, plastic viscosity, air content, and density at fresh state. Formwork pressure was monitored in a vertical channel with 4 pressure sensors flush mounted only a few millimeters from the surface of the concrete. Maximum lateral pressures were measured at Sensor 2 in the channel with a reading of 113.92 kPa at mid height, and Sensor 4 measured maximum vertical pressure at the base of 176.43 kPa which indicates nearly hydrostatic behavior of the high-fluidity mixtures. Regression analysis showed a strong inverse correlation with yield stress (R² = 0.89) and plastic viscosity (R² = 0.91) with pressure development, because higher yield stress and viscosity consistently showed lower pressures and more rapid decay. Returns on slump flow, V-Funnel time, l-box ratio, air content, and fresh density all revealed additional relationships which further supports the overall influence of dynamic flowability and structural build-up. The practical applications achieve a demonstration that can inform SCC mix design parameters while controlling fresh pressure and reducing risk of over-designed formwork and the enhanced safety of technical operations.